ANALYSIS OF SELLING PRICE FIXING AT UD. TWO BLESSING FURNITURE IN MASOHI CITY CENTRAL MALUKU REGENCY - Yuliarti Abdul Kadir; T. E. Siahaya; M. Sahureka (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2022)
This study aims to determine the pricing at UD. Berkah Dua Furniture for each type of product produced and knowing what factors influence the pricing. The method used in this study is a cost-based pricing method consisting of Cost Plus Pricing, Mark-Up Pricing and Selling Price Determining, where the data examined in this study are the Balance Sheet, Profit and Loss Report and the price list set by the company. The results of the study shows that 28 furniture products have prices lower than the results of the analysis and the factors that influence the determination of the selling price are internal and external factors.